Programmed death‐ligand 1 is prognostic factor in esophageal squamous cell carcinoma and is associated with epidermal growth factor receptor. Issue 4 (25th April 2017) - Zhang, Wencheng; Pang, Qingsong; Zhang, Xiaodong; Yan, Cihui; Wang, Qifeng; Yang, Jinsong; Yu, Shufei; Liu, Xiao; Pan, Yi; Yuan, Zhiyong; Wang, Ping; Xiao, Zefen
Abstract : Programmed death‐ligand 1 (PD‐L1) expression either indicates immune inhibitory status or concurrent immune response. Although the relationship between PD‐L1 and clinical outcomes has been studied widely in recent years, its role in prognosis of esophageal squamous cell carcinoma (ESCC) remains unclear. Here, we assessed the significance of PD‐L1 in ESCC and its association with epidermal growth factor receptor (EGFR) and radiation response. We found that PD‐L1 was present both on the surface of tumor cells and tumor‐infiltrating immune cells. Patients with tumor‐infiltrating immune cell PD‐L1 expression had better survival. PD‐L1 expression on immune cells was an independent prognostic factor for patients with ESCC. PD‐L1 expression either on tumor‐infiltrating immune cells or tumor cells was negatively associated with EGFR expression. EGFR/PD‐L1 pairs could separate the survival between EGFR low/PD‐L1 positive and EGFR high/PD‐L1 negative groups. In ESCC cell lines with EGFR high expression, PD‐L1 expression was induced significantly when EGFR signaling was activated by radiation and was dramatically inhibited by an EGFR tyrosine kinase inhibitor. In conclusion, tumor‐infiltrating immune cell PD‐L1 expression is an independent prognostic factor for ESCC, and the association between EGFR and PD‐L1 is vital to determining survival. It is important to consider radiotherapy‐induced imbalance of pro‐tumor and anti‐tumor immune response. A combination of radiotherapy and PD‐L1‐targeted therapy could be a promising therapeutic strategy for ESCC patients. Abstract : Our study indicates that tumor‐infiltrating immune cell PD‐L1 expression is an independent prognostic factor for ESCC, and the association between EGFR and PD‐L1 is vital to determining survival. It is important to consider radiotherapy‐induced imbalance of pro‐tumor and anti‐tumor immune response. A combination of radiotherapy and PD‐L1‐targeted therapies could be a promising therapeutic strategy for ESCC patients.